Warunki prowadzenia działalności gospodarczej w opinii jeleniogórskich podmiotów gospodarczych - wyniki badań ankietowych - Gargulińska, Maja; Gil, Adrianna; Szelągowska, Alicja; Szyrwiel, Daria; Woś, Agnieszka (Conditions for Conducting Business Activity According to Business Entities in Jelenia Góra - Survey Results, 2006)
This paper is a survey report and it has been written within projects conducted by Pro Futuro, the Student Scientific Group of Economy and Public Administration. The survey was aimed at identification and assessment of the most basic elements of a local business environment, which actually constitute the conditions for conducting business activity. The survey structure included questions concerning technical infrastructure, natural environment, attitudes of local authorities, the local real estate market, the local labour market, the institutional business environment, as well as problems and perspectives for entrepreneurs. The feedback seems to reveal both positive and negative sides of the local business atmosphere.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1124, s. 472-483